La transición entre el paradigma de la sustentabilidad y el reconcomiendo de la naturaleza como sujeto de derecho - Fernández, Cristian Hernán (Universidad Nacional del Litoral, 2021)
The fact that the genesis of this pandemic is linked to an episode of zoonosis in Wuhan indicates the need for a paradigm shift that places human beings in harmony with nature. Which coordinates should we follow to advance in this direction? We are still far from the sumak kawsay or suma qamaña that are present in Ecuador and Bolivia respectively. Their translations from quechua and aymara into english mean «good living» and «living well». In the last years we have witnessed in Argentina the appear ance of new regulations whose center of gravity has been forest and glaciers. These laws could mean that there is a transition between the sustainability paradigm and the recognition of rights of nature in Argentina.